El conocimiento matemático del profesor acerca de la parábola: Diseño de un instrumento para su investigación - Advíncula Clemente, Elizabeth Milagro (2020)
Research in mathematics education usually focuses on sharing results from the application of instruments to obtain data. Even though these instruments are usually described in the methodology section, their development process tends to not be transparent for the reader. The objective of this paper is to study this problem and describe in detail the process of creating a questionnaire based on the MTSK model, in order to explore the teacher's knowledge of parabolas, understood as conic sections. We present the design of a qualitative instrument that allows for the approximation of the teacher's mathematical knowledge of parabolas, emphasizing on the use of theory, as well as both internal and external triangulation, as key elements in the methodological design. The main contribution of this paper is to give guidelines for the design of questionnaires based on the MTSK model, which can be taken into account regardless of the mathematical contents.